Purple Urine Bag Syndrome: A Benign Condition Seen in a Young Patient with Hematological Malignancy - Sen, Ankita; Dolai, Tuphan Kanti; Mandal, Prakas Kumar; De, Rajib (Archives of Clinical and Medical Case Reports, 2020)
Purple urine bag syndrome (PUBS) is a rare benign condition seen mainly in elderly female patients who are immobilized or have chronic kidney diseases and have a long-standing urinary catheterization. Very rarely PUBS has been noted in patients with hematological malignancies. Here, we highlight a rare case of a young female patient with Acute Lymphoblastic Leukemia who developed PUBS. Understanding this entity is important as this often leads to undue concern among patients and their caregivers. <gdiv></gdiv>